Developing a Digital Flipbook Picture Storybook (Where Is Bibi Hiding?) as a Learning Media for Early Childhood Reading Skills - David Triatna, David Triatna; Nur Cahyati Ngaisah; Rachman, Budi (Early Childhood Research Journal (ECRJ), 2025)
This study aims to develop a digital flipbook picture storybook titled “Where Is Bibi Hiding?” as an interactive learning media to enhance early childhood reading skills. The research was conducted at TK PKK Maguwoharjo and employed the 4D development model (Define, Design, Develop, Disseminate). The digital flipbook was created using Canva and Heyzine Flipbook, focusing on readability, visual attractiveness, and age-appropriate content for children aged 5–6 years. The one-group pretest–posttest design was used to analyze the effectiveness of the media. The results show that the digital flipbook successfully increased children’s motivation to read, improved letter recognition, and supported word comprehension. Teachers also reported that the media encouraged more active participation and engagement during learning activities. Overall, the digital flipbook picture storybook is considered feasible, practical, and beneficial as a learning media for early childhood reading development.